HOPE FAMILY PROGRAM FOR MUSLIM SOCIETY WELFARE: EVIDANCE FROM HOPE FAMILY WEST PEKALONGAN REGENCY - Khusnul Marom; Tamamudin Tamamudin; Hendri Hermawan Adinugraha (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
This research has a purpose to describe the implementation mechanism of the Family Hope Program (PKH) in West Pekalongan Regency and to determine the level of welfare of the PKH recipients in West Pekalongan Regency. The method used in this research is qualitative with a field research approach. Sources of data in this study are program implementers and recipients of the PKH as well as scientific publications and research reports related to public policies such as PKH. Data collection methods in this study are in-depth interviews, observation, and documentation. Technique and data analysis in this research are data collection, data reduction, data display, and conclusion drawing and verification. The results of the study concluded that the effectiveness of PKH in West Pekalongan Regency. PKH in Pekalongan which was started in 2015-2020 which aims to alleviate poverty, one of which is in West Pekalongan Regency which started in 2015 has been running effectively. The effectiveness of this program is due to the precise targeting of participants and the effective allocation of PKH funds by PKH participants to make PKH efficient and in accordance with PKH goals, so as to reduce and alleviate poverty in Pekalongan, especially West Pekalongan Regency. From an Islamic perspective, this program has the value of justice, responsibility has been carried out well because PKH officials have found accuracy in determining the recipient of assistance by PKH officers, the responsibility for assistance and the accuracy of the date and amount of aid distributed in the District of West Pekalongan.